Enviromental Monitoring of Land Subsidence in The Coastal Area of Padang City Using Sentinel 1 Sar Dataset - Fajrin, Fajrin; Almegi, Almegi; Bakari, Aljunaid; Ramadhan, Risky; Antomi, Yudi (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The land surface in the Padang City is thought to be experiencing a continuous relative subsidence due to natural processes and man-made activities. Factors that affect land subsidence include earthquakes, sea level rise, infrastructure development, sediment transport, and excessive use of groundwater sources. The purpose of this research is to map the rate of land subsidence which is processed from the Sentinel 1-A radar, satellite imagery using the Differential Synthetic Aperture Radar (DInSAR) method. The data used are two pairs of Sentinel-1A level 1 Single Looking Complex (SLC) imagery which were acquired in 2018 and 2019. Image processing is carried out by filtering and multilooking techniques on Synthetic Aperture Radar (SAR) images. The following process changes the phase unwrapping to the ground level phase using phase displacement. Land subsidence in 2018–2019 from DInSAR processing reached -10.5 cm / year. The largest land subsidence occurred in North Padang with an average of -7.64 cm/year. Land subsidence in the Padang City, which is located near the estuary, is due to the nature of the alluvial sediment material. The use of Sentinel 1 SAR remote sensing data can provide important information in the context of mitigating land subsidence in the Padang City. Therefore, we need the right policies to handle future land subsidence cases. Land subsidence mapping is one of the factors that determine the vulnerability of coastal areas to disasters